KinectFusion for faces: real-time 3D face tracking and modeling using a Kinect camera for a markerless AR system - Macedo, Márcio Cerqueira de Farias (2016)
Submitted by Márcio Macedo (marciocfmacedo@hotmail.com) on 2016-12-06T04:26:56Z No. of bitstreams: 1 KinectFusion for Faces Real-Time 3D Face Tracking and Modeling Using a Kinect Camera for a Markerless AR System.pdf: 1064809 bytes, checksum: f6ce7d932b4cff2d3ef3ae3a16f8c202 (MD5)